Reseña de Gonzalo Lamana, «How “Indians” Think. Colonial Indigenous Intellectuals and the Question of Critical Race Theory», Tucson, The University of Arizona Press, 2019, 238 pp. ISBN 978-0-8165-3966-6 - Fernando Rodríguez Mansilla (Hipogrifo: Revista de Literatura y Cultura del Siglo de Oro, 2020)
Reseña de Gonzalo Lamana, How “Indians” Think. Colonial Indigenous Intellectuals and the Question of Critical Race Theory, Tucson, The University of Arizona Press, 2019, 238 pp. ISBN 978-0-8165-3966-6